Relationship Between Homocysteine and Carotid Artery Stenosis in Ischemic Stroke (Bangladesh Journal of Neuroscience, 2013)
Background: Epidemiologic studies have identified hyper-homocysteinemia as a possible risk factor for atherosclerosis. The aim of my study was based on evaluation of relationship between homocysteinemia with carotid artery stenosis in ischemic stroke patients.Methods and materials: It was a prospective observational study conducted in the Department of Neurology, Sir Salimullah Medical College & Mitford hospital, Dhaka. Thirty six consecutive patients with ischemic stroke were analyzed by serum total homocysteine, total cholesterol, HDL-cholesterol, LDL-cholesterol, triglyceride and extracranial Doppler ultrasonography and vascular risk factors were recorded. Equal number of controls of same ages were compared with the case group.Result: Mean fasting blood sugar, serum fasting total cholesterol (TC), serum fasting Low density lipoprotein (LDL) were significantly higher in case group (p=0.001). Serum TC and LDL had a positive correlation with serum homocystine (p=0.001). Serum High density lipoprotein (HDL) had a negative correlation (p=0.718) and serum triglyceride (TG) had a negative correlation (p = 0.182). Total plasma fasting homocysteine level in case group was 21.89 ± 9.38 ìmol/l and control group was 12.31 ± 3.27 ìmol/l, (p=0.001). Elevated fasting homocysteine level was found in 75.0% of the ischemic stroke patients and in 16.67% of healthy controls (p=0.001).On the basis of clinical evaluation and results of imaging studies, etiological classification of the ischemic stroke patients were made, where 36.1% cases were small artery disease, 38.9% large artery disease, 8.3% cases cardioembolic and in 16.7 % other causes. Among the cases, carotid duplex study was found normal in seven cases (19.4%), Group 1 findings in seven cases (19.4%), group 2 findings in eight cases (22.2%), group 3 findings in thirteen cases (36.1%) and group 4 findings in one case (2.8%). All abnormal carotid duplex findings were significantly higher among cases with elevated level of homocysteine (p=0.001, 0.001, 0.001).Conclusion: The incidence of hyperhomo-cysteinemia is higher in ischaemic stroke cases than that in age-sex matched healthy controls. Hyperhomocysteinemia in ischaemic stroke patients has been determined as vascular risk factor in our study. Significant correlation has been found between homocysteine concentration and intraluminal thickness and carotid artery stenosis.Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 1-9